DINAMIKA PERMASALAHAN KLASIK DALAM PENYELENGGARAAN PELAYANAN PUBLIK OLEH PEMERINTAH DESA - Dita Fisdian Adni; Nina Yuslaini (GEMA PUBLICA : Jurnal Manajemen dan Kebijakan Publik, 2019)
The Village Government is the spearhead in implementing existing government functions. Government functions according to Ryas Rasyid itself are four, namely Service, Development, Empowerment, and Regulation. The function that will be focused in this paper is the function of the service) carried out by the Village Government, namely the Village Head, Village Secretary and Other Village Devices to the Village Community. There are various services available at the Village Office, such as a cover letter for the management of Electronic Citizenship Cards, Family Cards, Birth Certificates, Death Certificates, Police Records and others. Although the services provided at the Village Office are only limited to a cover letter, good and satisfying services are a demand of the village community and must be fulfilled by village officials everywhere. This Conceptual Idea was created with the aim of identifying classic problems in the implementation of public services by the Village Government so that appropriate solutions can be found to answer these problems. There are so many classic problems that occur in the services provided by village government officials. For example, there are still village officials who do not have the ability to listen to complaints made by the village community about the services provided by the village officials. In addition, another classic problem is the ethics and attitude of the village officials in providing services to the community that are still not good. Of course with the ethics and attitude that is not good from the village apparatus, the community becomes uncomfortable in dealing with village officials. Classic problems like this are undeniably still found in many Village Offices throughout Indonesia. A formulation is needed so that the classic problems can be gradually lost and no longer become a disease in the Services carried out by the Village Government